Effects of ultrasound-assisted high temperature-pressure treatment on the structure and allergenicity of tropomyosin from clam (Mactra veneriformis) - Yachun Chen; Guifang Tian; Liwen Wang; Yaxin Sang; Jilu Sun (Food Chemistry: X, 2023)
Tropomyosin (TM) is the major allergen in clams. This study aimed to evaluate the effects of ultrasound-assisted high temperature-pressure treatment on the structure and allergenicity of TM from clams. The results showed that the combined treatment significantly affected the structure of TM—converting the α-helix to β-sheet and random coil, and decreasing the sulfhydryl group content, surface hydrophobicity, and particle size. These structural changes caused the unfolding of the protein, disrupting and modifying the allergenic epitopes. The significant reduction in the allergenicity of TM was approximately 68.1% when treated with combined processing (P < 0.05). Notably, an increase in the content of the relevant amino acids and a smaller particle size accelerated the penetration of the enzyme into the protein matrix, resulting in strengthening the gastrointestinal digestibility of TM. These results prove that ultrasound-assisted high temperature-pressure treatment has great potential in reducing allergenicity, benefiting the development of hypoallergenic clam products.